RESULTS OF INVESTIGATION OF TICK-BORNE INFECTIONS IN MONGOLIA - D. .. Abmed; Zh. .. Bataa; D. .. Anu; M. A. Khasnatinov; G. A. Danchinova; P. .. Nimidavaa; D. .. Nimahuu (Acta Biomedica Scientifica, 2012)
During 1999-2011 we conducted the collaborative research in Northern, Central and Eastern Mongolia. Several tick-borne infections were revealed in ticks and. human patients. Most important of them are tick-borne encephalitis, Lyme disease, tick-borne rickettsiosis, human granulocytic anaplasmosis and. babesiosis. The importance, risk of infection and. spread of tick-borne diseases in Mongolia are discussed in the paper.